A comparison of curfew and noncurfew violators using a self-report delinquency survey - Lersch, Kim Michelle (American journal of criminal justice, 2000)
The present study examines one city’s experience with a juvenile curfew ordinance. It compares characteristics of youths detained by the police for curfew violation with teenagers who did not have such police contact. Selfreport data reveal curfew violators admit committing more minor and serious delinquency, as well as status offenses, than noncurfew violators. Curfew violators also disclose higher victimization levels. Implications deriving from these observations are discussed.